2019
DOI: 10.1016/j.abd.2019.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Malassezia spp. in HIV-positive patients with and without seborrheic dermatitis

Abstract: BackgroundMalassezia, a skin saprophyte, is frequently isolated from patients with seborrheic dermatitis, which is one of the most common dermatoses in HIV-infected patients. Its role in pathophysiology has not been defined.ObjectiveTo determine whether patients living with HIV and seborrheic dermatitis have more Malassezia than those without seborrheic dermatitis.MethodThis is an descriptive, observational, prospective cross-sectional study to which all adult patients living with HIV that attend the infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
0
15
0
3
Order By: Relevance
“…The most recent study of Moreno-Coutino et al showed very similar results (rate of Malassezia isolation from patients with CD4+ counts > 500, 200-499, and < 200 cells/mm −3 was 60%, 27%, and 13%, respectively). Interestingly, patients with SD did not show this correlation in their study 39 . www.nature.com/scientificreports/ Another explanation is antifungal prophylaxis in immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The most recent study of Moreno-Coutino et al showed very similar results (rate of Malassezia isolation from patients with CD4+ counts > 500, 200-499, and < 200 cells/mm −3 was 60%, 27%, and 13%, respectively). Interestingly, patients with SD did not show this correlation in their study 39 . www.nature.com/scientificreports/ Another explanation is antifungal prophylaxis in immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 80%
“…The most recent study of Moreno-Coutino et al showed very similar results (rate of Malassezia isolation from patients with CD4+ counts > 500, 200–499, and < 200 cells/mm −3 was 60%, 27%, and 13%, respectively). Interestingly, patients with SD did not show this correlation in their study 39 . A possible explanation of this association is the disequilibrium of concurrent microbiota of skin due to the extensive treatment of viral, bacterial, and fungal dermatoses in neutropenic patients.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In some quantitative culture studies, the density of Malassezia was found to be higher in the skin of HIV patients compared to non-HIV controls [68]. One recent study in particular reported that the positive culture rate and density of Malassezia were very high in 30 HIV patients with seborrheic dermatitis (76.7%) compared to 30 HIV patients without seborrheic dermatitis (50%) [69]. This high rate could be explained by the number of CD4 cells present in the patients, as in the seborrheic dermatitis patients, 24 had <500 CD4 cells including nine with <200 CD4 cells.…”
Section: Malassezia and Hiv Infectionmentioning
confidence: 99%
“…Em humanos, espécies do fungo Malassezia fazem parte da microbiota da pele e, portanto, o equilíbrio populacional do fungo é fundamental para a saúde deste órgão. Assim, como em outros animais, quando em alta densidade populacional pode desencadear dermatites em humanos, sendo frequentes em indivíduos HIV positivos (MORENO-COUTINO et al, 2019).…”
Section: Introductionunclassified